Atypical presentation of Takayasu's arteritis in an adolescent - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Takayasu's arteritis is rarely seen in childhood. In addition, symptoms are nonspecific and diagnostic laboratory marker is unavailable. We hereby described an adolescent with an atypical presentation of Takayasu's arteritis. A 15-year-old girl was admitted to our clinic with the symptoms of weight loss, fever, back pain, and malaise since 2 months. Physical examination ended with normal vital signs, centiles and no other pathological findings. Laboratory findings showed increased acute phase reactants. Irregularities in the aortic wall and luminal narrowing of aorta were detected in magnetic resonance angiography. In conclusion, children with Takayasu's arteritis present with nonspecific symptoms. No laboratory test is diagnostic, whereas abnormalities in large vessels in radiology are specific for the disease. Mainstay of treatment is systemic steroids and immunosuppressants and outcome is worse in children than in adults.
Keywords: Adolescent; HLAB51; Takayasu's arteritis; Vasculitis